Correction to: Light-Activated Multilevel Resistive Switching Storage in Pt/Cs2AgBiBr6/ITO/Glass Devices - Tingting Zhong; Yongfu Qin; Fengzhen Lv; Haijun Qin; Xuedong Tian (Nanoscale Research Letters, 2022)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.